Project Digitalization-Based Learning Outcomes with the Project Based Learning model in the Vocal Technique Course - Heldisari, Hana Permata (Jurnal Pedagogi dan Pembelajaran, 2023)
Current job demands related to technology must be well-prepared, and the younger generation must be equipped with collaboration, creativity, critical thinking, and communication, which are related to the principles of project-based learning. This research aims to analyze the increase in creativity and skills in the vocal field, as well as the increase in the learning experience through digitalization. This research uses a quantitative approach with a pretest-posttest control group design, with PjbL as treatment. This research instrument is a skills test (performance test) used during the pretest and posttest to measure singing ability, which consists of phrasing, pitch, and dynamics. Data analysis used the independent sample t-test. The research results show that the PjBL learning model effectively improves the quality of skills and creativity in the digitalization-based vocal field. The increase in the experimental group was higher than the control group. Therefore, the PjBL model can be tested to be applied to other learning that includes skills and creativity. The PjBL model is critical for vocal technique courses to achieve learning objectives.